1980
DOI: 10.1126/science.7394533
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on Body Weight and Behavior in Developing Rats After Neonatal 6-Hydroxydopamine

Abstract: There is less hyperactive motor activity and better avoidance performance in rat pups treated with 6-hydroxydopamine as neonates and reared with vehicle-treated littermates than in pups reared in litters composed solely of other 6-hydroxydopamine-treated animals. Thus, in this experimental model of hyperactivity, an environmental manipulation provides an alternative to pharmacologic agents in reducing activity and improving learning performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
1

Year Published

1982
1982
1999
1999

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…It is noteworthy in this regard that PD35 rats were prepuber tal while PD56 rats were postpubertal (Baker 1979) Another possible explanation for our &ndings, that of delayed secondary neurodegenerative changes, can not be excluded. This possibility has been proposed to explain results of other studies that found changes in the expression of a neonatal lesion over time (Pearson et al 1980;Saji and Reis 1987). However, there is a very important difference between our study and these ear lier reports.…”
Section: Discussioncontrasting
confidence: 41%
“…It is noteworthy in this regard that PD35 rats were prepuber tal while PD56 rats were postpubertal (Baker 1979) Another possible explanation for our &ndings, that of delayed secondary neurodegenerative changes, can not be excluded. This possibility has been proposed to explain results of other studies that found changes in the expression of a neonatal lesion over time (Pearson et al 1980;Saji and Reis 1987). However, there is a very important difference between our study and these ear lier reports.…”
Section: Discussioncontrasting
confidence: 41%
“…Previous research has shown that control pups are seriously affected as a consequence of rearing in litters with manipulated pups. 10 It is conceivable that the repeated isolation paradigm exerted a highly disruptive effect on the dam that was translated to both groups of pups. Clinically, research has shown that it is the caregiver's response after a significant separation that is the critical variable in determining any enduring effects.…”
mentioning
confidence: 99%
“…In a previous study (Pearson et al, 1980), we noted that pups reared under conditions where half were vehicle and half 6-OHDA treated were considerably less active than pups reared in litters composed of all normal littermates. We would speculate that those vehicle pups reared under conditions where half their littermates had been affected by the neurotoxin, but only 3 other pups were normal, would be at a decided competitive advantage for food, and would tend to be less active than when having to compete with 7 normal littermates.…”
Section: Discussionmentioning
confidence: 95%
“…Recent experiments in our laboratory indicate that these dopanline-depleted pups are remarkably sensitive to environmental manipulations (Pearson, Teicher, Shaywitz, Cohen, Young, & Anderson, 1980;Teicher et al, 1981). Thus, 6-OHDA pups reared only with other 6-OHDA animals are more active than similarly depleted pups who are reared with normal animals.…”
mentioning
confidence: 96%
See 1 more Smart Citation